Beta‐2 microglobulin as a significant prognostic factor and a new risk model for patients with diffuse large B‐cell lymphoma. Issue 4 (30th May 2016) - Kanemasa, Yusuke; Shimoyama, Tatsu; Sasaki, Yuki; Tamura, Miho; Sawada, Takeshi; Omuro, Yasushi; Hishima, Tsunekazu; Maeda, Yoshiharu
Abstract: Previous reports have evaluated the prognostic value of serum beta‐2 microglobulin (B2MG) level in patients with non‐Hodgkin lymphoma. However, its role in predicting clinical outcome of patients with diffuse large B‐cell lymphoma (DLBCL) in the rituximab era has not been extensively investigated. Here, we evaluated the prognostic value of B2MG and proposed a new prognostic model including B2MG for patients with DLBCL. A total of 274 patients with newly diagnosed de novo DLBCL were retrospectively analyzed. We defined the best cutoff value as 3.2 mg/L by using a receiver operating characteristic curve. Patients with a B2MG level ≥3.2 mg/L had significantly lower overall survival (OS) and progression‐free survival than those with a B2MG level <3.2 mg/L (3‐year OS, 50.9% vs. 89.4%, p  < 0.001; 3‐year progression‐free survival, 45.3% vs. 79.7%, p  < 0.001). Multivariate analysis showed that B2MG, age, performance status, and Ann Arbor stage were independent prognostic factors for OS. We developed a new prognostic model consisting of these four significant factors. We stratified patients into four‐risk groups: low (L, 0 factor), low‐intermediate (LI, 1–2 factors), high‐intermediate (HI, 3 factors), high (H, 4 factors). This new prognostic model showed better risk discrimination compared with the National Comprehensive Cancer Network‐International Prognostic Index (5‐year OS: 100% and 23.4% vs. 100% and 27.1%, in L and H risk groups, respectively). Our study suggested that B2MG level is a significant prognostic factor in patients with DLBCL. A new prognostic index composed of age, performance status, stage, and B2MG could stratify the outcomes of patients with DLBCL effectively and appears to be a valuable risk model for these patients. Copyright © 2016 John Wiley & Sons, Ltd.